Long‐term, durable, absolute Psoriasis Area and Severity Index and health‐related quality of life improvements with risankizumab treatment: a post hoc integrated analysis of patients with moderate‐to‐severe plaque psoriasis. (17th March 2022) - Gooderham, M.; Pinter, A.; Ferris, L.K.; Warren, R.B.; Zhan, T.; Zeng, J.; Soliman, A.M.; Kaufmann, C.; Kaplan, B.; Photowala, H.; Strober, B.
Abstract: Background: Risankizumab has demonstrated durable, high rates of efficacy in patients with moderate‐to‐severe plaque psoriasis as assessed by the achievement of relative Psoriasis Area and Severity Index (PASI) improvement and Dermatology Life Quality Index (DLQI) 0/1. Objectives: The aim of this post hoc analysis is to assess the achievement of absolute PASI thresholds and related improvements in health‐related quality of life (HRQoL) in patients with moderate‐to‐severe plaque psoriasis treated with (i) risankizumab compared with ustekinumab, and (ii) long‐term (>52 weeks to 172 weeks) risankizumab. Methods: Data from patients randomised to 150 mg risankizumab or 45 or 90 mg ustekinumab in replicate randomised controlled trials UltIMMa‐1 and UltIMMa‐2 were analysed for the achievement of absolute PASI thresholds PASI ≤ 3, PASI ≤ 1, and PASI = 0, time to achieve these thresholds, and combined PASI and DLQI endpoints. Data from pat ients initially randomised to risankizumab who continued on risankizumab in the open‐label extension study LIMMitless were analysed for the achievement of absolute PASI levels, mean DLQI scores, and DLQI 0/1. Results: Significantly greater proportions of patients treated with risankizumab compared with ustekinumab achieved PASI ≤ 3, PASI ≤ 1, and PASI = 0, as well as combined endpoints for absolute PASI and DLQI [(PASI ≤ 3 and DLQI ≤ 5) or (PASI ≤ 1 and DLQI 0/1)]. The median time to first achieve PASI ≤ 3, PASI ≤ 1, and PASI = 0 was significantly lower for risankizumab‐treated patients compared with ustekinumab‐treated patients. Among patients treated with long‐term risankizumab, more than 90% achieved PASI ≤ 3 though week 172 and more than 80% achieved DLQI 0/1. Low absolute PASI scores corresponded with low mean absolute DLQI scores through week 172 of continuous risankizumab treatment. Conclusions: Risankizumab treatment demonstrated high rates of rapid and durable efficacy as measured by absolute PASI thresholds and improvements in patient HRQoL.